Psicologia amefricana: escrevivências de grupos oprimidos para uma práxis libertadora - Mendes, Mayara Ferreira (2023)
This research sought to affirm the existence of an Amefrican Psychology, based on the centralization of black and indigenous epistemologies and their critical historicity, especially with regard to their movements and productions of knowledge in Brazilian, Latin American and Afro-diasporic territory. From Amefricanity as a counterpoint to the knowledge historically made official by colonial and imperialist Western psychology, he sought to think about methodological paths through samba as an escrevivência exercise. Finally, it aimed to promote a dialogue through the rescue of thinkers who once produced a counter-colonial knowledge, namely: the political-cultural category of Amefricanity, the Psychology of Liberation and the Kaingang Psychology.